A new highly dimorphic genus of Sminthuridae (Collembola: Symphypleona) from Brazil - Zeppelini, Douglas; Brito, Roniere A.; Zampaulo, Robson; Lima, Estevam C.a. (Zootaxa, 2020)
A new genus and two new species of Sminthurinae are described. Keratosminthurus tapigu gen. nov. sp. nov. and K. calamitosus sp. nov. show a combination of features that redefines the subfamily Sminthurinae, such as a pair of sminthuroid chaetae, unguis without cavity, nine apical chaetae on tibiotarsus, 11 or more anterior dental chaetae, fourth antennal segment clearly subdivided into many (18 or more) subsegments, and asymmetric apex of mucro. The new genus also presents a striking sexual dimorphism, with modifications on male apical organ of antennal segment III, spines on the clypeus and special organs on the interocular area.